Brexpiprazole for the Treatment of Schizophrenia in Adults: An Overview of Its Clinical Efficacy and Safety and a Psychiatrist’s Perspective - Watanabe Y; Yamada S; Otsubo T; Kikuchi T (Dove Medical Press, 2020)
Yoshinori Watanabe,1 Sakiko Yamada,2 Tempei Otsubo,3 Toshiaki Kikuchi4 1Himorogi Psychiatric Institute, Tokyo, Japan; 2Medical Affairs, Otsuka Pharmaceutical Co. Ltd, Tokyo, Japan; 3Department of Psychiatry, Tokyo Women’s Medical University Medical Center East, Tokyo, Japan; 4Department of Neuropsychiatry, Keio University School of Medicine, Tokyo, JapanCorrespondence: Yoshinori WatanabeHimorogi Psychiatric Institute, 2-31-2 Ichigayatamachi, Shinjuku-ku, Tokyo 162-0843, JapanTel +81-3-5946-8586Email watanabe@himorogi.orgAbstract: While the prognosis of patients with schizophrenia has dramatically improved after the advent of chlorpromazine, the antipsychotics currently available are so numerous that it has become a challenge for psychiatrists to choose from among these drugs for each patient presenting for care. In addition, while numerous studies show that an effective antipsychotic should be continued indefinitely to prevent relapses or worsening, many patients appear to have difficulty remaining on any drug thus initiated. Brexpiprazole, a dopamine D2 receptor partial agonist, appears to provide a unique profile that has much to offer in this light. Specifically, this novel drug is potentially better suited for long-term use, with decreased risk of extrapyramidal side effects, hyperprolactinemia, weight gain, psychosis, insomnia, akathisia, nausea/vomiting or restlessness, thus potentially facilitating patients’ reintegration into society. Indeed, brexpiprazole has been shown in randomized, double-blind, placebo-controlled trials to have proven efficacy not only in improving the symptoms of schizophrenia but in preventing relapses. It is also suggested in both short- and long-term studies that brexpiprazole offers a favorable safety and tolerability profile. This review also includes a proposed treatment algorithm incorporating brexpiprazole, based on the clinical trial results available, as well as on the authors’ clinical experience, where brexpiprazole may be best used as a drug of first choice for the treatment of schizophrenia. Thus, overall, brexpiprazole appears to play a more significant role in the treatment of schizophrenia than other antipsychotics.Keywords: brexpiprazole, dopamine D2 receptor partial agonist, efficacy, safety, schizophrenia, treatment algorithm